Leadership Style Impact toward Employee Performance at ABC Hotel - Wiguna, Anak Agung Made Restu Adi; Diwyarthi, Ni Desak Made Santi; Kalpikawati, Ida Ayu (Multidisciplinary Journal of Education , Economic and Culture, 2025)
This study investigates the impact of leadership style on employee performance at ABC Hotel. A total of 152 employees participated as respondents, selected through a saturated sampling method. Data were collected using structured questionnaires with 26 statement items measured on a five-point Likert scale. Statistical analyses, including simple linear regression, t-tests, and the coefficient of determination, were conducted using SPSS software. The findings reveal that leadership style exerts a positive and significant influence on employee performance, explaining 81.4% of performance variance, while the remaining 18.6% is attributable to other factors not examined in this study. These results emphasize the strategic role of leadership in enhancing organizational performance in the hospitality sector.